The Conclusion of an International Agreement by the Holy See - Romanko, Agnieszka (PRAWO i WIĘŹ, 2025)
The concordat is an international, bilateral agreement concluded between the supreme authorities of a State and the Catholic Church (represented by the Apostolic See) on the basis of a partnership between the parties. In practice, apart from the term ‘concordat’, other terms, such as ‘convention’ or ‘treaty’, are used to designate the international agreement to which the situation of the Catholic Church on the territory of a particular state is the object. In the procedure for concordat conclusion, the Holy See applies not only the relevant regulations stipulated in international law (especially the Vienna Convention on the Law of Treaties), but the Catholic Church’s own law (the 1983 Code of Canon Law). Therefore, the procedure for concluding a concordat can be divided into the following stages: 1) the granting of full authority to negotiate and adopt the text of an international agreement and to conduct negotiations; 2) the authentication of the text and the initialling of the international agreement; 3) the signing, ratification and exchange of ratification documents; 4) the promulgation and entry into force of an international agreement.